2020
DOI: 10.3390/f11040407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GF2 and SPOT6 Imagery on Canopy Cover Estimating in Northern Subtropics Forest in China

Abstract: Canopy cover is an important vegetation attribute used for many environmental applications such as defining management objectives, thinning and ecological modeling. However, the estimation of canopy cover from high spatial resolution imagery is still a difficult task due to limited spectral information and the heterogeneous pixel values of the same canopy. In this paper, we compared the capacity of two high spatial resolution sensors (SPOT6 and GF2) using three ensemble learning models (Adaptive Boosting (AdaB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Although SVM has the advantage of handling high-dimensionality data and does well with a limited training dataset [86], it performed poorly in comparison with RF in this study. GDboost exhibited severe overfitting and returned unreliable predictions, although the literature reported the GDBoost model performed better than RF when estimating forest coverage [87]. It may be concluded that GDBoost presented major flaws in modeling highly correlated hyperspectral data.…”
Section: Discussionmentioning
confidence: 96%
“…Although SVM has the advantage of handling high-dimensionality data and does well with a limited training dataset [86], it performed poorly in comparison with RF in this study. GDboost exhibited severe overfitting and returned unreliable predictions, although the literature reported the GDBoost model performed better than RF when estimating forest coverage [87]. It may be concluded that GDBoost presented major flaws in modeling highly correlated hyperspectral data.…”
Section: Discussionmentioning
confidence: 96%
“…Although SVM has advantage of handling high dimensionality data and do well with a limited training dataset (Ma et al 2019), it performed poorly in comparison with RF in this study. GDboost exhibited severe overfitting and returned unreliable prediction although literature reported GDBoost model performed better RF when estimating forest coverage (Zhou et al 2020a). It may be concluded that GDBoost present major flaws in modeling highly correlated hyperspectral data.…”
Section: Discussionmentioning
confidence: 99%
“…The GDboost Algorithm tries to match the residual error of the new predictor with the previous one, while the Adaboost algorithm corrects the unfitness of the training instance through the previous training. The main difference between GDboost and Adaboost was how they deal with the underfitted values (Zhou et al 2020a). The number of trees (ntree) and learning rate (learning_rate) were tuned in AdaBoost and GDBoost models.…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%
“…Table Ⅰ shows the relevant information of each band of Landsat 8. However, many platforms on satellites are only equipped with visible and near-infrared bands, such as ZY-3 [34] and GF-2 [35], which provides limited feature information to detect clouds in remote sensing imagery and make the task more difficult. In order to cover the cloud detection tasks on most of optical satellite platforms, only four spectral bands-Band 2 to Band 5 are used in this work.…”
Section: A Landsatmentioning
confidence: 99%